Mulberry leaf ameliorate STZ induced diabetic rat by regulating hepatic glycometabolism and fatty acid β-oxidation - Lv, Bohan; Liu, Siyuan; Li, Yaqi; Li, Zhigang; An, Yongcheng; He, Changhao; Zhang, Huilin; Huang, Yan; Fu, Wanxin; Ma, Quantao; Zhao, Baosheng (Frontiers in Pharmacology, 2024)
Type 2 diabetes (T2D) is a metabolic disorder marked by disruptions in glucolipid metabolism, with numerous signaling pathways contributing to its progression. The liver, as the hub of glycolipid metabolism, plays a pivotal role in this context. Mulberry leaf (ML), a staple in traditional Chinese medicine, is widely utilized in the clinical management of T2D. Synthesizing existing literature with the outcomes of prior research, it has become evident that ML enhances glucose metabolism via multiple pathways. In our study, we induced T2D in rats through a regimen of high-sugar and high-fat diet supplementation, coupled with intraperitoneal injections of streptozotocin. We subsequently administered the aqueous extract of ML to these rats and assessed its efficacy using fasting blood glucose levels and other diagnostic indicators. Further, we conducted a comprehensive analysis of the rats' liver tissues using metabolomics and proteomics to gain insights into the underlying mechanisms. Our findings indicate that ML not only significantly alleviated the symptoms in T2D rats but also demonstrated the capacity to lower blood glucose levels. This was achieved by modulating the glucose-lipid metabolism and amino-terminal pathways within the liver. ACSL5, Dlat, Pdhb, G6pc, Mdh2, Cs, and other key enzymes in metabolic pathways regulated by ML may be the core targets of ML treatment for T2D.